Cambodia Rice : Export Potential and Strategies - International Finance Corporation (International Finance Corporation, Phnom Penh, 2017)
In 2010, Cambodia exported 40,000 metric tons of rice. In 2013, Cambodia exported nearly 400,000 metric tons ofrice to 66 countries. A ten-fold increase in just three years. Moreover, in only five years, Cambodia moved from apaddy to a milled rice exporter, and is now well on the way to evolving from a commodity trader to a demand driven export marketer. The evolution is evident in both the product and the process, with the sector now equipped with modern milling capacities, both in terms of volumeand quality management. This includes the introduction of Food Safety certification programs vital for penetrating international markets. Such progress will contribute substantially to the government’s rice sector policy of exporting one million tons of rice in 2015. This publication will present strategies and opportunities for Cambodian rice as an export product. It will illustrate how the Cambodia rice sector can improve its product image and how and where it can better place its rice in international markets given a more detailed analysis of its current and potential customers.